Research of the Converter Control Possibilities in the Grid-tied Renewable Energy Power Plant - Ramonas, C.; Adomavicius, V. (Elektronika ir Elektrotechnika, 2013)
Results of research of the converter control possibilities in the grid-tied renewable energy power plant are presented in this paper. Converter of the power plant consists of the DC chopper and the grid-tied inverter connected in series. Quality of the converter operation depends both on the DC chopper and inverter operation. Two ways of the converter operation control were researched: control of the DC chopper operation and control of the grid-tied inverter operation. Combination of both ways of the converter operation control has to be applied in order to achieve maximum available power production and the best parameters of the converter operation quality, such as maximum available efficiency of the power plant and minimum total harmonic distortion factor. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5891